Postpartum depression and mother–offspring conflict over maternal investment - Gunst Annika; Sundén My; Korja Riikka; Boddy Amy M; Kotler Jennifer; Paavonen E Juulia; Uusitupa Henna-Maria; Karlsson Linnea; Karlsson Hasse; Antfolk Jan (United Kingdom, 2025)
Background and objectives
As the mother–offspring relationship is central to human reproduction, postpartum depression symptoms are difficult to explain in evolutionary terms. We proposed that postpartum depression might arise as a result of evolutionary mother–offspring conflict over maternal investment, and investigated the association between postpartum depression symptoms, infant night waking, maternal sleep disturbance and breastfeeding frequency.
Methodology
We conducted a cross-sectional analysis using survey responses at 6 months postpartum from 1598 Finnish mothers. We hypothesized that infant night waking at 6 months postpartum would be associated with postpartum depression symptoms, and that this association would be mediated by maternal sleep disturbance and a higher breastfeeding frequency.
Results
Infant night waking was moderately associated with postpartum depression symptoms, and this association was mediated by maternal sleep disturbance (R2=0.09). Contrary to our prediction, we found that increased breastfeeding was associated with less postpartum depression symptoms.
Conclusions and implications
We conclude that postpartum depression symptoms might partly be the result of increased maternal fatigue stemming from high offspring demands on maternal investment, but that this is not due to the metabolic strain from increased breastfeeding. Studying postpartum depression from the mother–offspring conflict perspective can potentially improve our understanding of the involved behavioral processes of both mother and offspring, and allow interventions designed to benefit the well-being of both parties.
Lay Summary: We proposed that postpartum depression is due to an evolutionary conflict between mother and infant, where the infant tires the mother to delay the arrival of a sibling. We found a link between infant night waking and postpartum depression, mediated by the mother’s sleep, but not by breastfeeding frequency.